MODEL KOLABORASI TQM DALAM PEMENUHAN TRIDHARMA PERGURUAN TINGGI - Tria Citra Listiani Mukti; Ade Iriani; Yari Dwikurnaningsih (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
The tridharma of higher education in the form of education, research, and community service is the mandate of the legislation for universities. In implementing tridharma, universities should adapt to the development and needs of the community as well as science and technology (Science, Technology and the Arts). It can hardly be fulfilled by a university alone because of the growing needs of the society where all branches of science need to be integrated and connected. This study explained how collaboration could be applied in universities with a TQM approach. TQM has been widely used in various organizations and has proven its success for this approach was chosen in developing the existing collaboration model. Literature analysis method of TQM and collaboration was used in this study. The result is collaboration in fulfilling the Tridharma of higher education by using the TQM approach in a model stage could help organizations achieve previously agreed goals and adapt to existing science and technology needs.